Impact of Covid-19 on Retail Investor Investment Preferences - Suwardi Suwardi; Daniel Adi Setya Rahardjo (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2022)
Main Objective: This research aims to calculate the impact of the Covid 19 pandemic on the investment choices of retail investors by using the stock market as a benchmark. In addition to these objectives, there are several other objectives to evaluate the impact of Covid-19 on stock investment preferences by retail investors in the stock market, to understand whether retail investors are compliant to invest money in stocks by considering the effects of the pandemic identifying retail investor stock preferences after Covid-19 and factor the causes, and analyze the change in returns provided by investment in stocks based on the effects of Covid-19. Background problem: The role of the covid-19 pandemic in changing retail investment preferences has been speculated on since it was first recorded in 2020. The Covid-19 pandemic has caused various consequences that affect investor preferences and subsequently change investment behavior. Novelty: Investor preferences were affected enough by the covid-19 pandemic to change during the global lockdown timeframe. These preferences have been linked to several intrinsic and extrinsic factors that range from personal reasons to investment characteristics and performance in the stock market.